HUBUNGAN ANTARA MINAT MENGIKUTI PEMBELAJARAN PBL (PROBLEM BASED LEARNING) DENGAN MOTIVASI MENINGKATKAN PRESTASI PADA MAHASISWA TINGKAT I AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Endang Dwi Ningsih; Ratna Indriati; Magdalena Putri S. (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Problem Based Learning (PBL) is an instructional model that thestudents involved in problem solving by scientific methods, so the students learnthe knowledge related to the issued also the problem solving skill as well.The purpose of the study was to determine the relation between interest inlearning the PBL with motivation in increasing the learning achievement on thefirst year students of the Nursing Academy Panti Kosala Surakata.Subjects of the study by correlation method was held on April-Mei 2013, thesubject were 140 first year student of the Nursing Academy Panti KosalaSurakarta.The results shows:1.There was any relation between interes in learning the PBLwith motivation in increasing the learning achievement on the first year studentsof the Nursing Academy panti Kosala Surakarta, analized by X2 count > X2 table(188,321 > 13,277) with a significant level 0,01 (1%). 2. The determinationcoefficient value is 0,796 indicate that interested in learning the PBL influence tothe motivation in increasing learning achievement as 79,6% and the rest as20,4% influenced by the other else variables non model.Keyword : Interested in learning and the motivation in increasing learning.